2011
DOI: 10.4028/www.scientific.net/amr.409.751
|View full text |Cite
|
Sign up to set email alerts
|

INCONEL 718 Recrystallization in the Delta Supersolvus Domain

Abstract: An experimental study of compression tests at high temperature and different engineering strains was carried out on INCONEL 718 above the delta phase solvus. The objective is to investigate the mechanical behaviour in relation with the microstructure evolution. After deformation the samples were quenched with helium gas to avoid metadynamic recrystallization (MDRX). The quench efficiency is discussed by microstructural and hardness comparison. During forging process and without MDRX, there is generally a compe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 16 publications
(27 reference statements)
0
5
0
Order By: Relevance
“…A previous analysis proved that this transition starts from E ≈ 0.06 for a lower deformation rate on the same material. It has been shown that this transition corresponds to the nucleation of recrystallized grains [15]. This result will be used in the numerical part of this study.…”
Section: Mechanical Behaviourmentioning
confidence: 89%
See 1 more Smart Citation
“…A previous analysis proved that this transition starts from E ≈ 0.06 for a lower deformation rate on the same material. It has been shown that this transition corresponds to the nucleation of recrystallized grains [15]. This result will be used in the numerical part of this study.…”
Section: Mechanical Behaviourmentioning
confidence: 89%
“…It should be noted that the identification of the material parameters of the polycrystalline model were determined during the first deformation step, since it was previously proved that no dynamic recrystallization occurred for a deformation less than 0.06 [15]. Experimental and numerical stress-strain curves are given in Figure 9.…”
Section: Mechanical Behaviourmentioning
confidence: 99%
“…However, with increased temperature, the δ-phase becomes unstable and dissolves in the matrix, and thus causes rapid grain-coarsening. 3,24 Some studies claim that the δ-phase dissolves in the matrix and diffuses into the voids and vacancies of grain boundaries before RX begins. However, a few studies concluded that the δ-phase precipitates along the grain boundaries as well as at shear bands following the nucleation of new grains.…”
Section: Introductionmentioning
confidence: 99%
“…However, a few studies concluded that the δ-phase precipitates along the grain boundaries as well as at shear bands following the nucleation of new grains. 3,15,24,25 Interestingly, some investigations that are focused on the fatigue, fracture, and creep behaviour of IN718, reported that the unique morphology of the δ-precipitates causes cracks to propagate in zigzag pattern both within the grains and along the grain boundaries, and thus help in improving the creep-fatigue life of the alloy. [26][27][28] From the above discussion, it is clear that the formation and the control of δ-phase play a crucial role in the processing and performance of IN718.…”
Section: Introductionmentioning
confidence: 99%
“…Dynamic and post-dynamic recrystallization is among the most important phenomena impacting the microstructure of hot-forged components. The influence of the thermomechanical forging conditions on dynamic recrystallization (DRX) kinetics and on the DRX grain size is relatively well established [1][2][3][4][5][6][7][8], and can even be predicted using either physical or empirical models [9][10][11][12][13][14][15]. However, previous studies have shown that post-dynamic evolutions may also considerably impact the final microstructure [12,[15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%